2007
DOI: 10.3758/bf03193615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of working memory capacity on mental set due to domain knowledge

Abstract: The present set of studies examines how working memory capacity (WMC) relates to performance on a Remote Associates Task (RAT), originally designed by Mednick (1962) as a quantifiable creative problem solving assessment. The source of fixation was manipulated across two sets of RAT items. One set was neutral with no specific fixation embedded in them, while the second set was baseball-misleading, designed so that prior knowledge of baseball would lead to an incorrect solution attempt (Wiley, 1998). WMC scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 20 publications
(49 reference statements)
2
51
0
Order By: Relevance
“…2 (Spring 2012) be aided by attentional control under some circumstances. Several studies have shown that RAT problem solving ability is generally correlated with WMC (Kane, 2004;Ricks, Turley-Ames & Wiley, 2007), although this could be for many reasons including individual differences in verbal aptitude that also are generally correlated with WMC. Yet, effective inhibitory function may be especially important when a solver needs to deal with fixation induced by the presence of incorrect associates within the context of problem solving (Smith & Blankenship, 1991;Storm & Angello, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…2 (Spring 2012) be aided by attentional control under some circumstances. Several studies have shown that RAT problem solving ability is generally correlated with WMC (Kane, 2004;Ricks, Turley-Ames & Wiley, 2007), although this could be for many reasons including individual differences in verbal aptitude that also are generally correlated with WMC. Yet, effective inhibitory function may be especially important when a solver needs to deal with fixation induced by the presence of incorrect associates within the context of problem solving (Smith & Blankenship, 1991;Storm & Angello, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a positive correlation between working memory capacity and RAT performance attention (Ricks, Turley-Ames, & Wiley, 2007) is consistent with this possibility, since it may reflect a common contribution from the executive control of attention (Ricks, et al, 2007), which involves effortful processing, for instance, in order to resolve conflict (Fernandez-Duque, Baird, & Posner, 2000). The role of control of attention is also highlighted by the finding that high working memory capacity no longer benefits RAT performance when RAT problems are specifically constructed to activate and focus attention on strong misleading cues in memory based on a person's prior domain-specific knowledge (Ricks, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the possession of domain knowledge generally improves problem solving performance (e.g. Chase & Simon, 1973;Chi, Feltovich, & Glaser, 1981;Gobet & Charness, 2006;Voss, Greene, Post, & Penner, 1983; but see Ricks, Turley-Ames, & Wiley, 2007;Wiley, 1998, for instances in which domain knowledge can have negative effects on problem solving). In a review of the literature on superior cognitive performance due to expertise, Ericsson and Kintsch (1995) concluded that domain knowledge has important effects on the working memory system in the context of domain-related cognitive tasks.…”
Section: Introductionmentioning
confidence: 97%